Data supporting the angiotensin II activates MEL18 to deSUMOylate HSF2 for hypertension-related heart failure - Chih-Yang Huang; Chia-Hua Kuo; Pei-Ying Pai; Tsung-Jung Ho; Yueh-Min Lin; Ray-Jade Chen; Fuu-Jen Tsai; V. Vijaya Padma; Wei-Wen Kuo; Chih-Yang Huang (Data in Brief, 2018)
In association with the published article “Inhibition of HSF2 SUMOylation via MEL18 upregulates IGF-IIR and leads to hypertension-induced cardiac hypertrophy” (Huang et al., 2017) [1], this data article contains information about deSUMOylation of HSF2 on lysine 82 on angiotensin II (ANG II) -induced cardiac hypertrophy, which is mediated by MEL18. Isolated adult human whole heart tissue showed MEL18-mediated HSF2-IGF-IIR pathway is upregulated in hypertension human heart, compared to health human heart.